2021
DOI: 10.1002/lt.25960
|View full text |Cite
|
Sign up to set email alerts
|

Histidine‐Rich Glycoprotein Alleviates Liver Ischemia/Reperfusion Injury in Mice With Nonalcoholic Steatohepatitis

Abstract: Hepatic ischemia/reperfusion injury (IRI) is a major complication of liver surgery and transplantation, especially in patients with nonalcoholic steatohepatitis (NASH). The mechanism of NASH susceptibility to IRI has not been fully clarified. We investigated the role of liver‐produced histidine‐rich glycoprotein (HRG) in NASH IRI. A NASH mouse model was established using C57BL/6J mice fed a methionine‐choline–deficient diet (MCDD) for 6 weeks. The MCDD and standard diet groups were exposed to 60 minutes of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Fga (fibrinogen alpha-chain) promotes the synthesis of the alpha portion of fibrinogen and is upregulated in response to tissue injury to help clot formation and induce inflammation (Gabay and Kushner, 1999;Ryu et al, 2015). Hrg is highly connected with the other genes in the module and its protein facilitates blood coagulation, activates lymphocytes and supports healthy liver functioning (Guo et al, 2020;Johnson et al, 2014;Poon et al, 2011). Shifts in the expression of these genes in subordinates with high CORT is likely to occur in response to accumulating injuries in subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Fga (fibrinogen alpha-chain) promotes the synthesis of the alpha portion of fibrinogen and is upregulated in response to tissue injury to help clot formation and induce inflammation (Gabay and Kushner, 1999;Ryu et al, 2015). Hrg is highly connected with the other genes in the module and its protein facilitates blood coagulation, activates lymphocytes and supports healthy liver functioning (Guo et al, 2020;Johnson et al, 2014;Poon et al, 2011). Shifts in the expression of these genes in subordinates with high CORT is likely to occur in response to accumulating injuries in subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…However, steatotic hepatocytes reduce HRG production under hypoxia/reoxygenation conditions, promoting neutrophil activation and NETosis. HRG administration ameliorates hepatic IRI in NASH mouse models by attenuating neutrophil infiltration [81].…”
Section: Cellular Crosstalk Between Neutrophils and Nonimmune Cells I...mentioning
confidence: 99%
“…Both neutrophils and NETs negatively correlate with the expression of histidine-rich glycoprotein (HRG) in mouse models of liver IRI. Overexpression of HRG in mice suppressed neutrophil infiltration and NET formation in the liver, thus reversing hepatic IRI ( 129 ). Another study demonstrated that hydroxychloroquine inhibits NET formation and alleviates liver IRI in mouse models of liver ischemia-reperfusion ( 48 ).…”
Section: Nets In Hepatocellular Carcinomamentioning
confidence: 99%